Women as Industry 4.0. entrepreneurs: Unlocking the potential of entrepreneurship in higher education in STEM-related fields - Dolores R. Serrano; Ana Isabel Fraguas-Sánchez; Elena González-Burgos; Paz Martín; Catalina Llorente; Aikaterini Lalatsa (Journal of Innovation and Entrepreneurship, 2023)
Industry 4.0 is the realization of digital transformation including enhanced productivity and flexibility due to real-time decision-making, which is possible due to the high-speed internet, the internet of things, and smart machines capable of autonomously exchanging information, triggering actions, and controlling each other independently. A high level of education and skills is increasingly more important in the job market over the next years necessitating finding a balance among behavioural, technological, analytical, and entrepreneurial skills. EU and governments worldwide should invest in closing the gender gap in science, technology, engineering, and mathematics (STEM) education as this will directly impact the economic growth. Even though there is some progress in the hiring percentage of women in large technological companies, a clear glass ceiling in leadership roles is still remains. Here, we have undertaken a pilot study at University Complutense of Madrid (UCM, Spain) aimed at empowering women in academia to transition from the "publish or perish" paradigm towards creating and protecting their intellectual property to close the gender gap in STEM fields and leadership roles as well as training to fuel the development of innovative start-ups addressing societal challenges. A total of 20 participants inclusive of UCM staff and postgraduate and postdoctoral researchers were enrolled after successfully obtaining at least a score of 5 out of 10 in custom-made Entrepreneurial competency test provided by Business and Professional Women Association (BPW, Spain) and theGrowBox Innovation Ltd. The study, approved by the UCM ethical committee, was conducted after participants engaged and completed a training programme on "Enterpreneurship in STEM-related fields in Higher Education" aimed to introduce the participants to the entrepreneurial world. This involved a structured training programme covering the (i) business canvas design; (ii) development of minimum viable product (MVP); (iii) market evaluation; (iv) finance analysis using the Growbox platform; (v) introduction to venture capital; and (vi) human resources management followed by individual mentoring sessions prior completion of their business plans that were pitched to a panel of mentors and BPW representatives. Finally, all participants completed an anonymous survey of 12 open questions to evaluate the impact of the training in awakening the entrepreneurial spirit in academic researchers in Higher Education in STEM-related fields. Three-quarters of participants were novices in terms of Entrepreneurship, but all participants after the programme presented a complete business plan. The three points that women identified as prohibitive factors were lack of self-confidence, ambition, and knowledge in the fields of patent filing, finance and marketing. Participants were likely to initiate their own start-up in the next five years, but had mixed fillings regarding the complexity of the process. Nine months after the course ended, four out of 20 participants have been successful in attracting initial funding to support the initiation of a start-up involving protected intellectual property and managed to secure an award to provide them with office space to build their company. The long-term impact of this training programme will need to be followed up. Entrepreneurial training is crucial to be embedded in curricula for postgraduate and if possible undergraduate students to pursue a major transformation targeting the STEM-related fields in Higher Education to enable women in becoming key participants and leaders in the Industry 4.0 era.
Keywords: 650; Higher Education; Industry 4.0; Science; technology; engineering; and mathematics (STEM) education; Women entrepreneurship